Monte-Carlo simulations of clinically realistic respiratory gated 18F-FDG PET: Application to lesion detectability and volume measurements. Issue 1 (January 2015) - Vauclin, S.; Michel, C.; Buvat, I.; Doyeux, K.; Edet-Sanson, A.; Vera, P.; Gardin, I.; Hapdey, S.
Graphical abstract